2016
DOI: 10.1161/strokeaha.116.014139
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Noninvasive In Vivo Compound Ultrasound Strain Imaging Using Histologic Plaque Vulnerability Features

Abstract: A therosclerotic carotid plaque rupture is a major cause of cerebrovascular mortality and morbidity. The proneness of a plaque to rupture is mainly related to its composition and geometry.1,2 Rupture-prone plaques typically contain a medium to large necrotic/lipid-rich core, which is separated from the lumen by a thin fibrous cap, whereas stable plaques have a thicker cap and often no necrotic/lipid-rich core. 1,2 Furthermore, vulnerable plaques frequently present with intraplaque hemorrhage, a high concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…Strain parameters (RS and CS) were calculated from the radiofrequency data using custom made software written in Matlab R2014 (The MathWorks Inc., USA) [10, 19]. First ultrasonic frames were identified that corresponded to the systolic and diastolic phases (maximum and minimum lumen diameter, respectively) in an M-mode view of the image line that crossed the vessel lumen center.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain parameters (RS and CS) were calculated from the radiofrequency data using custom made software written in Matlab R2014 (The MathWorks Inc., USA) [10, 19]. First ultrasonic frames were identified that corresponded to the systolic and diastolic phases (maximum and minimum lumen diameter, respectively) in an M-mode view of the image line that crossed the vessel lumen center.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several RF-based strain techniques specifically designed to evaluate arterial wall strain have been developed [1015]. Some of these techniques have already been validated against post-endarterectomy histology and/or magnetic resonance imaging derived plaque composition [1619]. In all of these validation studies patients with severe amounts of stenosis (>50%) were included.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue motion and deformation can provide information about the structure, composition and functioning of the tissue and changes in the dynamic behavior of tissue can be used as indicator of disease. For example, stiff regions in breasts are often related to cancers [11,12], the assessment of local arterial deformation provides information about the atherosclerotic progression and vulnerability of lesions [13][14][15][16], increased blood velocities indicate the presence of a stenosis in the vessel [17][18][19], and infarcted myocardial tissue shows changed deformation patterns as compared to healthy tissue [20].…”
Section: Introductionmentioning
confidence: 99%
“…One of them is functional assessment of the carotid vessel wall. Strain imaging holds the ability to quantify the mechanical deformation of the arterial wall induced by the pulsating blood and provides insight into the composition and morphology of the vessel wall, which is unavailable from ultrasonic imaging alone [2][3][4][5]. Therefore, strain imaging could reveal ongoing, frequently asymptomatic, pathological processes like plaque development.…”
Section: Introductionmentioning
confidence: 99%
“…With these techniques, it has been shown that arterial strain distribution correlates with histological composition of plaques in pigs [16] and in humans [2,17]. For intravascular imaging and non-invasive imaging in longitudinal planes, the US beam is aligned with the principal direction of deformation of the artery (radial for a concentric homogeneous artery), which implies a direct and accurate estimation of the strains in the principal direction using algorithms that only estimate the (axial) displacement component along the beam.…”
Section: Introductionmentioning
confidence: 99%